2019
DOI: 10.1016/j.conctc.2019.100446
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing control group allocation in randomized trials using dynamic borrowing of external control data – An application to second line therapy for non-small cell lung cancer

Abstract: BackgroundEnrollment of participants to control arms in clinical trials can be challenging. This is particularly an issue in oncology trials where the standard-of-care is shifting rapidly and several promising experimental treatments are undergoing phase III testing. Novel methods for utilizing external control data may mitigate these challenges, but applied examples are sparse. Here, we therefore illustrate how Bayesian dynamic borrowing of external individual patient level control data from similar clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…Thus our test of independence likely underestimated atezolizumab’s single-agent activity. To address this we used clinically observed differences in atezolizumab activity by line of therapy 28 to construct a synthetic arm - as recently discussed for NSCLC 30 - of first-line atezolizumab for nonsquamous NSCLC ( Figure 2k ; Supplementary Figure 1 ) and found that IMpower150 now closely matched the expectation of independence (Hazard Ratio 1.04, P = 0.46, n = 356; Figure 3a , dotted line denotes adjusted hazard ratio).…”
Section: Resultsmentioning
confidence: 98%
“…Thus our test of independence likely underestimated atezolizumab’s single-agent activity. To address this we used clinically observed differences in atezolizumab activity by line of therapy 28 to construct a synthetic arm - as recently discussed for NSCLC 30 - of first-line atezolizumab for nonsquamous NSCLC ( Figure 2k ; Supplementary Figure 1 ) and found that IMpower150 now closely matched the expectation of independence (Hazard Ratio 1.04, P = 0.46, n = 356; Figure 3a , dotted line denotes adjusted hazard ratio).…”
Section: Resultsmentioning
confidence: 98%
“…Thus, our initial test of independence likely underestimated atezolizumab's single-agent activity. To address this we used clinically observed differences in atezolizumab activity by line of therapy 28 to construct a synthetic arm -as recently discussed for NSCLC 30 -of atezolizumab for firstline treatment of nonsquamous NSCLC (Figure 2k; Supplementary Figure 1) and found that IMpower150 now closely matched the expectation of independence (Hazard Ratio 1.04, P = 0.46, n = 356; Figure 3a, dotted line denotes adjusted hazard ratio).…”
Section: Analyzing a Possible Case Of Additive Or Synergistic Drug Inmentioning
confidence: 98%
“…Thus, our initial test of independence likely underestimated atezolizumab's single-agent activity. To address this we used clinically observed differences in atezolizumab activity by line of therapy 28 to construct a synthetic arm -as recently discussed for NSCLC 30 We are therefore left with two competing hypotheses about the four-drug combination tested in IMpower150: (a) atezolizumab is slightly less active at second-line than first-line, and independent action explains the benefit of adding atezolizumab to bevacizumab plus carboplatin plus paclitaxel, (b) atezolizumab is equally active at first and later lines of therapy and drug additivity or synergy is observed. Because atezolizumab is known to be more effective at the first-line of therapy in other NSCLC cohorts 28 we conclude that hypothesis (a) is more likely.…”
Section: Analyzing a Possible Case Of Additive Or Synergistic Drug Inmentioning
confidence: 99%
“…For example, prior work utilizing Bayesian dynamic borrowing identified that when historic data with similar patient demographics were combined, uncertainty was reduced significantly per each additionally included trial external control data source. 25 In contrast, when incongruent clinical trial data were combined, no additional improvement to uncertainty was noted regardless of the number of trials of external control data added.…”
Section: Is the Synthetic Control Data Set Sufficiently Reliable And Comprehensive?mentioning
confidence: 99%
“…Even if pertinent RCTs are not highly identical, much strength can still be gained. 25 Where it is either unethical or infeasible to enrol patients to a control intervention, external data should be selected from the best possible source of data and synthetic controls can be used as a substitute for an absent control arm. In this setting (often a rare disease setting), pertinent RCTs are typically not available.…”
Section: Did the Clinical Trial Include A Concurrent Control Arm Or Is The Synthetic Control Data The Only Control Data?mentioning
confidence: 99%